2006
DOI: 10.1016/j.cbpc.2006.03.002
|View full text |Cite
|
Sign up to set email alerts
|

Effect of calcineurin inhibitors on myotoxic activity of crotoxin and Bothrops asper phospholipase A2 myotoxins in vivo and in vitro

Abstract: Previous studies have shown that calcineurin activity plays a critical role in the myotoxic activity induced by crotoxin (CTX), a group II phospholipase A 2 (PLA 2 ) with neurotoxic and myotoxic actions. In order to address whether calcineurin is also important for the activity of nonneurotoxic group II PLA 2 myotoxins we have compared the effects of calcineurin inhibition on the myotoxic capacity of CTX and the nonneurotoxic PLA 2 s, myotoxin II (Mt II) and myotoxin III (Mt III) from Bothrops asper venom. Rat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 56 publications
0
6
0
Order By: Relevance
“…Receptors for myotoxins isolated from the venom of Oxyuranus scutellatus have been identified [15,16] and it has been suggested that the receptor of the Lys49 myotoxin is the VEGF (vascular endothelial growth factor) receptor itself [17,18]. The presence of specific plasma membrane receptors is also supported by the selectivity of some myotoxins for type I muscle fibers [19,20]. The finding that various snake myotoxins are more toxic to differentiated myotubes than to undifferentiated myoblasts [21,22] may indeed suggest the presence of specific toxin receptors in the differentiated, but not in the undifferentiated, cells.…”
Section: Introductionmentioning
confidence: 83%
“…Receptors for myotoxins isolated from the venom of Oxyuranus scutellatus have been identified [15,16] and it has been suggested that the receptor of the Lys49 myotoxin is the VEGF (vascular endothelial growth factor) receptor itself [17,18]. The presence of specific plasma membrane receptors is also supported by the selectivity of some myotoxins for type I muscle fibers [19,20]. The finding that various snake myotoxins are more toxic to differentiated myotubes than to undifferentiated myoblasts [21,22] may indeed suggest the presence of specific toxin receptors in the differentiated, but not in the undifferentiated, cells.…”
Section: Introductionmentioning
confidence: 83%
“…Moreover, BaV myotoxins are able to affect types I, IIA and IIB muscle fibers, whereas crotoxin is more selective towards oxidative types I and IIA fibers [36]; since tibialis anterior muscle is predominantly constituted by type II fibers [59] such difference might have implications in the mtDNA release. Differences in the mechanism of action of crotoxin and BaV myotoxins were shown by their different myotoxic response to the pretreatment of animals with calcineurin [60], an observation that might be related to the variable specificity towards different muscle fiber types.…”
Section: Discussionmentioning
confidence: 99%
“…c) An important consequence in muscles is that the damaged mitochondria release cell death mediators through the opening of the permeability transition pore [114]. This is suggested by the ability of cyclosporin A to abrogate myotoxicity induced by crotoxin [38] because cyclosporin A inhibits the opening of the permeability transition pore. If Ca 2+ -induced mitochondrial alterations and loss of function are relatively simple to detect in vivo, this may not be the case for other less-prominent intracellular organelles.…”
Section: Membrane Damagementioning
confidence: 97%
“…The binding of notexin to muscle cell plasma membrane has been documented by immunoelectron microscopy [37]. Furthermore, the ability of cyclosporin A, an inhibitor of calcineurin, to suppress the myotoxic action of crotoxin can be interpreted on the basis of the calcineurininduced shift of muscle fiber type to crotoxinsusceptible type I, slow oxidative fibers [38]. However, the identity of receptors remains elusive.…”
Section: Cell Bindingmentioning
confidence: 98%